Holocaust and its Aftermath through the lenses of Jewish and Roma families between women´s history and gender - Baloun, Pavel (Romano džaniben, 2022)
A critical essay on the volume Jewish & Romani Families in the Holocaust and its Aftermath edited by Eliyana R. Adler and Kateřina Čapková.